Perception-Induced Effects of Corporate Social Irresponsibility (CSiR) for Stereotypical and Admired Firms - Voliotis, Seraphim; Vlachos, Pavlos A.; Epitropaki, Olga (Frontiers in Psychology, 2016)
How do stakeholders react to Corporate Social Irresponsibility (CSiR)? What are the emotional mechanisms and behavioral outcomes following CSiR perception? The psychology of CSR literature has yet to address these important questions and has largely considered CSR and CSiR as the opposite poles of the same continuum. In contrast, we view CSR and CSiR as distinct constructs and theorize about the cognitive (perceptual), emotional, and behavioral effects of CSiR activity on observers (i.e., primary and secondary stakeholders) building on theories of intergroup perception. Specifically, building on the Stereotype Content Model (SCM; Fiske et al., 2002) and the BIAS map (i.e., Behaviors from Intergroup Affect and Stereotypes; Cuddy et al., 2007)—which extends the SCM by predicting behavioral responses—we make predictions on potential stakeholder reactions to CSiR focusing on two practice-relevant cases: (a) a typical for-profit firm that engages in a CSiR activity, (b) an atypical admired firm that engages in CSiR activity.